An investigation into the mechanisms of action of Revalor-S and Optaflexx in growing steers - Walker, D.K.; Higgins, James J.; Johnson, B.J.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to evaluate the interaction between steroidal implantation and feeding ractopamine on nitrogen retention, blood metabolites, and messenger RNA (mRNA) expression. Six Holstein steers (initially weighing 509 lb) were implanted or not with Revalor-S (120 mg trenbolone acetate plus 24 mg estradiol-17β), and all were fed no ractopamine for the initial 28 days and then 2 grams per steer daily of Optaflexx (200 mg/day ractopamine-HCl) on days 29 through 56. Implantation increased nitrogen retention. Optaflexx increased nitrogen retention in nonimplanted steers, but did not significantly increase retained nitrogen in implanted steers. Implantation increased serum insulin-like growth factor (IGF)-I concentration. Optaflexx, however, numerically decreased serum IGF-I concentrations. Implantation numerically increased IGF-I mRNA in the longissimus muscle, but expression of IGF-I mRNA was significantly decreased when Optaflexx was fed. Both growth promotants increased nitrogen retention in steers, but, despite perceived differences in their mode of action, the combination yielded a less than additive response for nitrogen retention.
Keywords: Beef; Revalor-S; Optaflexx; Steers